PT. CITRA VAN TITIPAN KILAT DI KOTA JAMBI 1980-2013 - Nurul Huda, Nur Agustiningsih (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2018)
Abstract The puprpose of this research to explain the existence of PT.Citra Van Titipan Kilat in Jambi City starting from the status of representative to become the main branch during the period 1980-2013. The research method used is historical method including heuristic stages, source critic, interpretation, and historiography. Historical sources used include: archives or company documents, books, theses, theses, and additional referrals from the internet, plus interviews with informants related to the research topic.The results showed that the existence of PT. Citra Van Titipan Kilat in Jambi City since under the management of Ratna Nilam and PT.Titipan Kilat Jambi as its business entity, showed progress in the form of expansion of service by establishing agents in Jambi City. Thus, both PT.Citra Van Titipan Kilat and PT. Jambi Express Fastness is equally beneficial in terms of financial benefits. But in its development can not be denied PT.Titipan Kilat Jambi faced with several other service companies that become competitors in the city of Jambi. Keywords: PT.Citra Van Titipan Kilat, Ratna Nilam, PT.Titipan Kilat Jambi, Representative, Main Branch. Company